(untitled) (Revista Latino-Americana de Enfermagem, 2011)
This systematic literature review evaluated the methodological quality of studies measuring noise in neonatal intensive care units. A manual and also electronic search in the Medline, Scielo, Lilacs, BDENF, WHOLIS, BDTD, Science Direct, NCBI and Scirus databases resulted in 40 studies that met the criterion "measuring noise in neonatal units and/or incubators". Experts in neonatology and acoustics validated the critical analysis instrument, which obtained a mean = 7.9 (SD=1.3). The inter-observer reliability in 18 articles resulted in an Intra-class correlation coefficient (ICC) of 0.89 (CI 0.75-0.95). The quality indicators were 50% better in those studies that measured noise only in the unit's environment and associated measuring strategies to the physical area. The results showed great methodological variability, which hindered comparability and raised the probability of bias. The conditions required to ensure internal and external validity were observed in few studies.